Diffusion‐Triggered Synthesis of Mg2Si Based on Infiltrated Silicon Structures in Molten Mg. Issue 1 (29th October 2021) - Heimann, Johann; Jost, Norbert
Abstract : Magnesium silicide (Mg2 Si) has many good properties and therefore shows a high application potential as thermoelectric material. Herein, the intermetallic layer growth behavior in the Mg–Si system is investigated. A process for synthesizing Mg2 Si on the surface of open‐pore cellular Si structures is developed. The structure is fabricated by investment casting and followed by infiltration of magnesium. Subsequently, magnesium silicide is obtained by a two‐step heat treatment. Complete synthesis of Si to Mg2 Si is achieved using a liquid–solid reaction between the liquid Mg and solid Si. The optimal heat treatment for the first step is at the eutectic temperature of 950 °C and for a duration of 120 min. The second treatment is at 1150 °C, slightly above the melting point of Mg2 Si, and the remaining Si is synthesized. The resulting microstructures are analyzed using a scanning electron microscope (SEM) and energy‐dispersive spectroscopy (EDS). Abstract : A process for synthesizing Mg2 Si on the surface of open‐pore cellular Si structures is investigated. The structure is fabricated by investment casting, followed by infiltration of magnesium. Complete synthesis of Si to Mg2 Si is achieved with a two‐step thermal treatment. The optimal temperature for the first step is at 950 °C and the second at 1150 °C.